Discourses of Subversion The Ethics and Aesthetics of Capoeira and Parkour - Fuggle, Sophie (Edinburgh: Edinburgh University Press, 2008)
RESUMEN: This article will examine the notion of subversive discourse found in both the Brazilian dance-martial art known as capoeira and the recent urban phenomenon called parkour, looking in detail at the origins and influences of the two disciplines. With reference to capoeira, I will argue that the linguistic structure which underpins the game provides the space for each capoeirista to develop his or her own creative expression or 'personality' within the framework of the discipline. When looking at parkour, I will consider the ways in which it embodies both the notion of flesh in Merleau-Ponty's later writings and how through such an understanding of their bodies and the space around them, practitioners of parkour, known as traceurs, are able to engage in what Foucault refers to as 'technologies of the self'.